INJURY RISK FACTORS IN CHILDREN AND YOUTH IN PHYSICAL / SPORTS ACTIVITY - Marina Dobnik (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Purpose: The aim of the article is to define the injury risk factors in physical/sports activity and how they may correlate. Methods: A systematic review of electronic databases MEDLINE, Google Scholar, ScienceDirect and Cinahl in May 2015 has provided potentially suitable articles, 10 of which were deemed original for a further detailed review. The studies include children and youth aged 0 to 19 and consider different possible injury risk factors in children in physical/sports activity. Results: The majority of article authors (7) in selected studies share the opinion that rather than in girls, injuries are more common in boys. One of the authors claims that the factor of gender carries no substantial emphasis. The highest number of physical/sports activity-related injuries occurs in older children and adolescents. One of the selected studies finds that overweight youth develop a higher risk of sports injuries. The opinions of the authors differ when it comes to the level of physical/sports activity. Some authors conclude that children who are more active suffer fewer injuries, while other authors believe the actively involved children to be subject to a higher number of injuries. Younger children (up to the age 12) are subject to injuries while involved in an unorganised type of activity, whether during active games outside or inside, walking or running freely. Older children and adolescents (aged above 12 years) sustain injuries more often in an organised type of activity. Conclusions: Given the selected studies we were not able to introduce general conclusions regarding the connection between various injury risk factors, since all studies partially differ from each other, regarding age range of study participants, geographical sampling, selected injury risk factors, and different injury definitions. It can be concluded that a higher level of physical/sports activity brings a higher risk of injury.